2006
DOI: 10.1007/bf02758303
|View full text |Cite
|
Sign up to set email alerts
|

Mantoux and contact positivity in tuberculosis

Abstract: The study also reflects that the extra pulmonary forms of tuberculosis seems to be more common in the pediatric population which constituted 79.8% of the cases included in the study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
17
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 11 publications
4
17
0
Order By: Relevance
“…Vijaysekaran et al have found that in their study Mantoux positivity in childhood TB varies from 21.2% to 53%. 12 Sputum examination was found to be positive in 9 cases (10%) similar to other studies. Older children were significantly associated with positive AFB.…”
Section: Discussionsupporting
confidence: 88%
“…Vijaysekaran et al have found that in their study Mantoux positivity in childhood TB varies from 21.2% to 53%. 12 Sputum examination was found to be positive in 9 cases (10%) similar to other studies. Older children were significantly associated with positive AFB.…”
Section: Discussionsupporting
confidence: 88%
“…11 Turan SI et al and Flora AL observed that 30% and 38.8% cases of tuberculoma had abnormal chest radiograph suggestive of tuberculosis, found similar to 30.7% children with abnormal chest radiographs among tuberculoma in our study group. 12,13 Our study has conducted on diverse population from remote areas with poor medical facilities and low socio economic status who are mostly a BPL card holder limiting the emergent and non-urgent neuroimaging at the time admission and on follow up.…”
supporting
confidence: 83%
“…Studies from India have reported culture positivity ranging from 32% to 37.7% [26][27][28] [30]. Higher rates in these studies have been attributed to the use of a combination of induced sputum and gastric lavage as specimens, as well as the use of a combination of one solid and one liquid medium.…”
Section: Discussionmentioning
confidence: 97%